تقلبات أسعار النفط وتنويع الصادرات في الجزائر -دراسة قياسية لحالة الجزائر باستخدام نموذج الانحدار الذاتي الموزع غير الخطي (nardl) للفترة (1995-2018)- - مكيديش, محمد; واسطي, أسماء (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الورقة البحثية إلى محاولة الكشف عن العلاقة التي تربط تقلبات أسعار النفط بتنويع الصادرات في الجزائر للفترة من 1995 إلى 2018 وذلك باستخدام نموذج الانحدار الذاتي الموزع غير الخطي (NARDL) الذي تزداد أهميته لالتقاط التأثيرات غير المتماثلة للعديد من المتغيرات الاقتصادية نظرا لأن التقلبات يمكن أن تكون سلبية أو إيجابية، وقد أسفرت النتائج على أن هناك علاقة غير متماثلة ما بين تقلبات أسعار النفط وتنويع الصادرات في الجزائر على المدى القصير والطويل، كما خلصت دراستنا إلى أن التركيز على قطاع النفط يعيق عملية تحقيق التنويع في الجزائر حيث أن ارتفاع التقلبات تقلل من تنويع الصادرات بينما انخفاضها يرفع من أداء التنويع. This research paper aims to try disclosing the relationship between oil price volatility and export diversification in Algeria for the period from 1995 to 2018 using a non-linear Autoregressive Distributed Lag (NARDL) model, which is becoming increasingly important to capture asymmetrical effects of many economic variables because of the volatility could be positive or negative. The results showed that there is an asymmetric relationship between oil price volatility and export diversification in the short and long run, Our study also concluded that the focus on the oil sector has impeded the process of diversification in Algeria as high volatility reduce export divercification while her Low raises the performance of diversification.
Oil price volatility and export diversification in Algeria A standard case study of Algeria using the Nonlinear Autoregressive Distributed Lag (NARDL) for the period (1995-2018)
Keywords: تنويع الصادرات ; تقلبات أسعار النفط ; الجزائر ; نموذج NARDL